2015
DOI: 10.1111/psq.12208
|View full text |Cite
|
Sign up to set email alerts
|

Agency Design, the Mass Media, and the Blame for Agency Scandals

Abstract: I investigate whether formal presidential authority over agencies moderates attributions of responsibility for agency activity. Using a survey experiment that manipulates news coverage of a major agency scandal, I find that providing details about formal presidential control in news coverage significantly increases attributions of responsibility to the president. I then explore broader questions of accountability by assessing mass media attention to agencies. I use a unique data set of over 150,000 newspaper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Therefore, cues can shape citizens’ perceptions of the prescriptions for a given event, where cues about the context may shape citizens’ expectations given the change in the environment. Information cues influence citizens’ blame attributions, especially when the information affects the controllability or distance from the event (Ruder , ). For example, blame is higher for a state governor who performs poorly when the state legislature is the same political party as the governor (Rudolph ), illustrating how cues influence perceptions of controllability.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Therefore, cues can shape citizens’ perceptions of the prescriptions for a given event, where cues about the context may shape citizens’ expectations given the change in the environment. Information cues influence citizens’ blame attributions, especially when the information affects the controllability or distance from the event (Ruder , ). For example, blame is higher for a state governor who performs poorly when the state legislature is the same political party as the governor (Rudolph ), illustrating how cues influence perceptions of controllability.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In a pair of studies that estimate the structure → blame model, Ruder (, ) tests two hypotheses concerning how details about the design of federal agencies affect the amount of blame that individuals attribute to the president for agency behavior. In the first, which focuses on antitrust enforcement by the Federal Trade Commission (FTC), Ruder () uses a survey experiment to examine whether information about the FTC's structural independence affects the amount of blame that subjects attribute to the president for FTC enforcement activities.…”
Section: Blame Attributionmentioning
confidence: 99%
“…In the second study, which focuses on oversight of the oil and gas industry by the Minerals Management Service (MMS), Ruder () uses a similar experiment to test whether subjects who are given information implying presidential control attribute more blame to President Barack Obama for the MMS's role in the Deepwater Horizon oil spill. Ruder finds that subjects in this “presidential control” condition do indeed attribute more blame to President Obama than subjects who are given no information implying presidential control of the MMS.…”
Section: Blame Attributionmentioning
confidence: 99%
“…Ruder (2014) varied the agency types in a survey experiment and found that participants were less likely to attribute blame to a U.S. President when there was no causallinkage present with an agency. Similarly, Ruder (2015) conducted an experiment concerning the Deepwater Horizon oil spill in the Gulf of Mexico and found that survey participants were more likely to attribute blame to the U.S. President if a causal-linkage was established. This research collectively suggests that blame associated with bad policy outcomes can be diffused when there is no clear causal-linkage at the Federal level, perhaps this is due to issue saliency at the Federal level with a greater clarity in hierarchy and program control.…”
Section: Literature Reviewmentioning
confidence: 99%